Paracetamol-induced hepatotoxicity in a malnourished patient: A case report - Sudhanshu Shukla; Tejashree Sridhar; Jayasheela Siddalingayya Hiremath; Sanathkumar B. Nyamagoud; Viswanatha Agadi Hiremath Swamy (MGM Journal of Medical Sciences)
Acetaminophen, an analgesic and antipyretic with a favorable safety profile, is used globally. However, excessive doses can lead to severe hepatotoxicity and acute liver failure. We present a case report that describes the unfortunate demise of a 48-year-old male patient with colon carcinoma who developed severe hepatotoxicity attributed to the administration of paracetamol following right radical hemicolectomy. Despite the patient receiving paracetamol at a dosage below the recommended limit under medical supervision, he experienced a rapid deterioration in liver function, leading to a cascade of life-threatening complications. The intricate interplay between medication administration and patient-specific factors emphasizes the ongoing need for the medical community to evolve and optimize treatment strategies for improved patient outcomes.